XXth century 2 plays - Jacob, Malou (Diliman, Quezon City University of the Philippines Press, 2009)
These two plays dissect the violence inflicted on Filipinos by Filipinos.
English and Tagalog.
Keywords: Philippine drama (English) -- 20th century; Filipino drama -- 20th century